Mobile-Aided Language Learning: Case Study of Using Smartphone Applications for Learning English: Pembelajaran Bahasa Berbantuan Ponsel: Studi Kasus Penggunaan Aplikasi Telepon Pintar untuk Belajar Bahasa Inggris - Khabib, Erfina Maulidah; Muliana, Suci (Politeknik Harapan Bangsa Surakarta, 2024)
This study intends to give more comprehensive information about smartphone apps that aid in learning English, offer substitute materials and teaching techniques to sharpen their language skills, and motivate both students and instructors to adopt cutting-edge teaching and learning strategies. The case study approach is selected because it permits a holistic and real-world perspective while concentrating on individual cases. According to the findings, English language learners utilise mobile applications because they would rather access different types of material and participate in social networking sites than focus on learning. This study shows that by providing simple access to English information that matches their interests, apps can help intermediate English learners improve their English skills.